British War-Time Control of Copper, Lead, and Zinc - Backman, Jules; Fishman, Leo (Quarterly Journal of Economics, 1941)
The change from a peace to a war-time economy, 211. — Scope of the present study, 212. — Pre-war preparations for control, 212. — The time schedule of war control, 214. — Methods of control: maximum prices, 216; priorities, 218; supply controls, 219; licenses, 222. — Organization and administration of control, 222. — Problems of control, 224. — Personnel, 225. — Priorities, 226. — Business practices, 228. — The London Metal Exchange, 230. — Small firms, 231. — Scrap metal, 232. — Administration of the control, 235. — Conclusions, 237.